Analısıs Nılaı Karakter Pedulı Sosıal Pada Fılm Kartun Alıf Dan Alya Untuk Siswa Sekolah Dasar - Dewi, Putry Aprilia; Arya Setya Nugroho (Jurnal Elementaria Edukasia, 2023)
In the modern era, anything can be done independently and with the help of technology. Bringing a lot of influence to the development of science and technology. Such as the fading sense of social care in each individual due to the impact of the development of technology. The purpose of this research is to describe the values of the socially caring character in the film Alif Alya, which is aimed at elementary school students. This study uses a qualitative research methodology, data analysis using reception analysis, data collection techniques using documentation as a data collection technique, and data analysis techniques by analyzing videos downloaded on Alif Alya's YouTube channel. The results of this study, the social care values contained in the film Alif Alya are able to cultivate at least three social care character values, namely Empathy, Helping, and Cooperation. The socially helpful nature of empathy is demonstrated in the actions of socially responsible people, which is consistent with the actions of children who appear to feel what other children are feeling. A type of social care known as collaborative social care requires teamwork to achieve specific goals. Social concern for helping others is shown by their compassion for children who act in a way that helps others without expecting anything in return.